Skrining Senyawa dari Tanaman Rhodomyrtus tomentosa (Aiton) Hassk terhadap SARS-CoV-2 ORF3a - Samsul Hadi (Jurnal Surya Medika (JSM), 2021)
The ORF3a protein from SARS-CoV has functions in terms of ion channel activity, modulates the trafficking properties of SARS-CoV spike (S) protein, increases fibrinogen expression in pulmonary epithelial cells, and induces apoptosis. So that research is needed to overcome the ORF3a experiment. The method in this research uses the computational screening method with autodok4 software. The results of this study resulted in free binding energy between Hassk Rhodomyrtus tomentosa (Aiton) and ORF3a compounds, namely: α-tocopherol-quinone (-5.86); blumeatin (-4.98); methyl cinnamate (-4.44); myricetin (-4.49); naringenin (-4.93); quercetin (-4,9); rhodomyrtone (-6); rhodomyrtosone B (-7.11); rhodomyrtosone C (-6.77); tetrahydroxyflavanone (-4.91); α-tocopherol A (-6.72); verimol K (-4.89); watsonianone A (-7.55). Based on the data obtained, the ligand with the most potential due to the stability of the bond is watsonianone A.